THE USE OF MIND MAPPING TECHNIQUE IN TEACHING WRITING DESCRIPTIVE TEXT - Susie Kusumayanthi; Amiruddin Abdul Malik (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
The research is entitled “The Use of Mind Mapping Technique in Teaching Writing Descriptive Text.” The aims of the research are to figure out how is mind mapping applied in teaching writing descriptive text and what are the students’ responses in teaching writing descriptive text using mind mapping technique. This research uses descriptive qualitative method. The respondent of this study are one teacher and five students in one of a Vocational High School 4 Padalarang. The instruments used to collect data are classroom observation and interviews. The result of data analysis showed that the teacher implemented all the steps of mind mapping technique in teaching writing descriptive text systematically during classroom activities and interview and the result of mind mapping makes by the students including (1) students uses central idea with picture. (2) Students uses keywords (3) Students uses branch. (4) Students uses curved line. (5) Students uses images or symbol (6) students uses colors. The research findings also showed the students’ responses in teaching writing descriptive text using mind mapping technique including helpful, meaningful, motivate learning, and provide learning satisfaction. Finally, the results of interviews suggest that the students loved this technique because it successfully motivated them to write descriptive texts in an enjoyable way, to improve their writing descriptive texts, to increase vocabulary and creativity, to arrange sentences and organize ideas. It is then recommended that mind mapping technique be used in teaching writing in different text types.